The Role of Pentahelix in Flood Disaster Risk Reduction in Cirebon City to Achieve Regional Security - Rivaldy, Mohammad; Sutisna, Sobar; Puto, Robertus Anugerah Purwoko; Kurniadi, Anwar; Kusuma, Kusuma; Wilopo, Wilopo (EQUATOR SINAR AKADEMIA, 2025)
Massive flooding in Cirebon City poses a significant threat to regional security, requiring a collaborative disaster risk reduction (DRR) approach. This study examines the Pentahelix model's role and effectiveness, which includes government, academics, businesses, communities, and media, in managing flood risks. Using a qualitative case study, researchers gathered data from the Cirebon City Regional Disaster Management Agency (BPBD) and other key actors through in-depth interviews and participant observation. The findings show that each Pentahelix actor plays a unique and complementary role, although challenges in coordination still exist. Effective initiatives, such as the